Intensive care in thoracic oncology. Issue 5 (11th May 2017) - Meert, Anne-Pascale; Grigoriu, Bogdan; Licker, Marc; Van Schil, Paul E.; Berghmans, Thierry
The admission of lung cancer patients to intensive care is related to postprocedural/postoperative care and medical complications due to cancer or its treatment, but is also related to acute organ failure not directly related to cancer. Despite careful preoperative risk management and the use of modern surgical and anaesthetic techniques, thoracic surgery remains associated with high morbidity, related to the extent of resection and specific comorbidities. Fast-tracking processes with timely recognition and treatment of complications favourably influence patient outcome. Postoperative preventive and therapeutic management has to be carefully planned in order to reduce postoperative morbidity and mortality. For patients with severe complications, intensive care unit (ICU) mortality rate ranges from 13% to 47%, and hospital mortality ranges from 24% to 65%. Common predictors of in-hospital mortality are severity scores, number of failing organs, general condition, respiratory distress and the need for mechanical ventilation or vasopressors. When considering long-term survival after discharge, cancer-related parameters retain their prognostic value. Thoracic surgeons, anesthesiologists, pneumologists, intensivists and oncologists need to develop close and confident partnerships aimed at implementing evidence-based patient care, securing clinical pathways for patient management while promoting education, research and innovation. The final decision on admitting a patient with lung to the ICU should be taken in close partnership between this medical team and the patient and his or her relatives. ICU should be proposed to lung cancer patients after discussion between the patient and the multidisciplinary team http://ow.ly/TWZ3308SB4g